Sharing indoor space: stakeholders' perspectives and energy metrics. Issue 1 (12th May 2020) - Francart, Nicolas; Höjer, Mattias; Mjörnell, Kristina; Orahim, Allanmikel Sargon; von Platten, Jenny; Malmqvist, Tove
The sharing of indoor space can improve space and energy efficiency. The drivers and barriers to space-sharing initiatives are investigated from the perspectives of building users and building sector practitioners, based on interviews and a workshop. The role of energy performance metrics in promoting space efficiency is further analysed through a literature review. From the users' perspective, space sharing can be understood through the interplay between tangible aspects ( e.g . concrete benefits derived from sharing), organisational aspects ( e.g . common decision processes and conflict resolution) and social aspects ( e.g . group identity and consensus on appropriate behaviours). From the perspective of architects and property owners, shareable spaces require features such as flexibility and multifunctionality. The design of such spaces is limited by regulatory issues ( e.g . building regulations poorly accommodate shared facilities) and business-related issues. One such issue is that building performance metrics normalised based on floor area do not incentivise the efficient use of space. A review of complementary metrics is provided, covering parameters such as number of users, layout, time of use, etc . Each metric serves a particular purpose; therefore, a set of complementary metrics can be used to support decisions at different phases of the building's life cycle. Practice relevance: Improving space efficiency ( e.g . by sharing indoor space) is a key strategy to meet simultaneously the future demand for facilities in cities and fulfil environmental objectives such as a reduction of climate change impact in the building sector. A clearer understanding of the specificities of space sharing is provided from the perspectives of building users and practitioners. This will assist practitioners to understand the needs of other stakeholders. Regulatory and business-related barriers to space-sharing initiatives are highlighted as a first step towards overcoming these barriers. Guidance is provided on complementary energy performance metrics appropriate for space efficiency. These metrics can be used to support various decisions during the different stages of a building's life cycle.